An Analysis of Writing Material in Senior High School Students’ Textbook - Vienna Christanty Limbong; Riska Evangelina Hutabarat; Desiana Bondar; Jefri Doloksaribu; Putra Buololo (EDUCARE, 2019)
This research aims to describe the writing activities used in entitled “The “Bahasa Inggris” Textbook” for eleventh grade. This research used qualitative method. The object in this research is the writing activities in the textbook. The research findings in English textbook entitled Bahasa Inggris for eleventh grade student of Senior High School, the researchers conclude that the textbook used Dialogue writing in the writing activities, in order that students can interact each other in improving social manner for they have asked questions to their partners, helping each other how to build a good writing skill.